Peran Pelatihan Kewirausahaan dalam Meningkatkan Kinerja Pedagang Pasar - Dorotea Sotizunidar Waruwu; Syamsul Hadi (Mahesa Research Center, 2026)
This article aims to provide an in-depth description of the role of entrepreneurship training in improving the performance of traders at Pasar Lanang Ambarawa, Semarang Regency. The study focuses on the limited managerial capacity and adaptability of traders in responding to traditional market dynamics. To address this issue, it applies theories of entrepreneurial competence development and a proactive mindset. Data were collected through interviews, observations, and documentation, and analysed qualitatively using a thematic approach. The findings indicate that entrepreneurship training enhances business management, marketing, product innovation, and service quality. Traders demonstrate more structured business practices, improved customer interaction, and better adaptation to market demand. However, the effectiveness of training is influenced by capital support, market facilities, and continuous mentoring. This study contributes to strengthening a context-based entrepreneurship training model for traditional market traders.